Legal Aspects of Digital Business Licensing: A Mixed-Methods Analysis of the OSS-RBA in Indonesia's Batam Free Trade Zone - Fadlan; E Arinda Chikita (HM Publisher, 2025)
The global trend of digital transformation in public administration has prompted significant legal and institutional reforms aimed at enhancing economic competitiveness. In Indonesia, this is exemplified by the 2021 launch of the Online Single Submission Risk-Based Approach (OSS-RBA), a centralized digital platform for business licensing. This study investigates the implementation of this system within the complex legal environment of the Batam Free Trade Zone (FTZ), a strategic economic hub characterized by regulatory dualism. The aim of this research is to critically evaluate the legal and commercial implications of the OSS-RBA's implementation in a Special Economic Zone. Its novelty lies in employing a rigorous mixed-methods approach to move beyond a simple efficiency analysis, providing a nuanced examination of the tensions between digital administrative reform and the foundational commercial law principles of legal certainty, procedural justice, and regulatory harmonization. This study utilized a convergent parallel mixed-methods design. The doctrinal legal analysis involved a systematic content analysis of Indonesia’s 1945 Constitution, Law No. 11 of 2020 (Omnibus Law), and Batam-specific regulations. The empirical component included a quantitative analysis of 245 licensing applications (2022-2023), three distinct surveys of business representatives and applicants (n=156, n=189, n=198), and qualitative data from structured interviews with 56 regulatory officials and legal practitioners, alongside focus groups with 45 business actors. A novel Business Legal Certainty Index (BLCI) was constructed and validated to measure regulatory predictability. The findings demonstrate that the OSS-RBA has yielded significant administrative efficiencies, reducing licensing processing times by up to 83.9% and increasing approval rates to 92.7%. This correlates with a 67.3% increase in Foreign Direct Investment in Batam post-implementation. However, the system is fraught with challenges. The study identified 23 specific legal inconsistencies between national and FTZ regulations, leading to jurisdictional ambiguity. Furthermore, the opacity of algorithmic decision-making raises significant administrative justice concerns, with only 45% of automated decisions providing a clear rationale, thereby limiting access to effective legal remedies. In conclusion, the OSS-RBA represents a critical step toward modernizing Indonesia's investment climate, but its success is contingent on substantial legal and institutional reform. To realize the full potential of digital governance, policymakers must prioritize comprehensive regulatory harmonization, amend administrative procedure laws to safeguard due process in an automated era, and strengthen institutional capacity.